The Innovation of Cake Learning Application on Student’s Speaking Ability at Tenth Grade of Senior High School - Titis Istikhomahningsih; Widyastuti; Slamet Setiawan (Universitas Islam Negeri Palopo, 2025)
Cake is an Android-based app that focuses on learning English but keeps it fun. There are many benefits of using this app because this app is completely free. This app can practice speaking, reading and even listening skills. The purpose of this study is to find out whether there is a significant effect between students' speaking ability before and after teaching using the classroom cake learning application X Senior High School. This study uses quantitative research. The design of this study was pre-experimental with a pre-test design and a one-group post-test design. This study took place from March to May 2023 at Senior High School. To collect data, researchers used an oral monologue test to determine students' speaking ability. The population includes all 10th grade students of Senior High School, and this study used one class as the research sample using convenience sampling technique, whereby the total sample was 33 students. Additionally, pretest, treatment, and posttest were used to collect data. The results of data analysis show that the average score of students after being taught with the Cake learning application (78.24) is higher than before being taught with the Cake learning application. Learning application Cake episode (57,64). It can be concluded that there is an influence between students' speaking ability before and after being taught using the cake learning application in class X Senior High School.